On generalized resolvents of Hermitian operators in Krein spaces - Derkach, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
Various classes of extensions and generalized resolvents of Hermitian operators acting in Krein spaces are described in terms of abstract boundary conditions.